Method for synthesizing iron oxide mesoscopic crystals by low-temperature mineralization of ferrihydrite

The synthesis of iron oxide mesoscopic crystals by mineralizing iron ore at near room temperature has solved the problem of high temperature in the preparation of traditional iron oxide, and achieved low-energy consumption and green-prepared iron oxide mesoscopic crystals with good lithium battery performance and uniform particle size.

CN118929771BActive Publication Date: 2025-04-15WUHAN UNIV OF TECH
View PDF 1 Cites 0 Cited by

Patent Information

Application Number
CN202411171508.8
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2024-08-26
Publication Date
2025-04-15
Estimated Expiration
2044-08-26

AI Technical Summary

Technical Problem

The preparation of traditional iron oxide requires high temperature conditions, and the synthesis of mesoscopic crystals usually depends on template etching and high temperature processing, making it difficult to achieve a green and low energy consumption preparation method.

Method used

Iron oxide mesoscopic crystals are synthesized by mineralization at near room temperature, and iron oxide nitrate nitrate and iron trichloride are used to react in a constant temperature water bath and oven. Iron oxide with a mesoscopic crystal structure is prepared through centrifugation, washing and freeze-drying.

Benefits of technology

The iron oxide mesogenic crystal is synthesized at low cost and low energy consumption at near room temperature. The product has good lithium battery performance and uniform particle size, providing a green and economical material preparation method.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN118929771B_ABST
    Figure CN118929771B_ABST
Patent Text Reader

Abstract

The present invention relates to a method for synthesizing iron oxide mesoscopic crystals by low-temperature mineralization of ferrihydrite, comprising the following steps: S1, adding ferric nitrate nine hydrate to deionized water, and then cooling to room temperature after reacting for a period of time under constant temperature water bath stirring; collecting precipitation by centrifugation, repeatedly washing with deionized water, and finally freeze drying to obtain ferrihydrite powder; dispersing the ferrihydrite powder into an aqueous solution to obtain a ferrihydrite solution; S2, adding ferric chloride and urea to deionized water, and continuously stirring to obtain a mineralization solution; adding the ferrihydrite solution dropwise under continuous stirring, and continuing to stir to obtain a mixed mineralization solution containing ferrihydrite; placing a reactor containing the mixed mineralization solution in a constant temperature oven for sufficient reaction and then naturally cooling to room temperature; collecting precipitation by centrifugation, and repeatedly washing with deionized water, and finally freeze drying to obtain an iron oxide mesoscopic crystal product. The iron oxide mesoscopic crystal material of the present invention is expected to be applied in the field of energy materials.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to new materials and application fields thereof, and more particularly to a method for synthesizing iron oxide mesoscopic crystals by low-temperature mineralization of ferrihydrite. Background Art

[0002] Natural materials can complete their structural formation processes at room temperature, developing exquisite microstructures that impart unique functions. This is the result of billions of years of evolution. However, in modern industry, the preparation of materials with similar properties often requires high temperatures and other conditions. In recent years, by studying natural manufacturing processes and the relationship between natural manufacturing processes and biological structures, a process-inspired biomimetic preparation technology has been developed, enabling the controlled preparation of inorganic materials at room temperature.

[0003] Jingjing Xie et al. used living clams as a natural biosynthesis platform to synthesize nitrogen-doped anatase TiO2 with a hierarchical pore structure at room temperature, and the powder had excellent photodegradation and photohydrogen production properties. (Jingjing Xie, et al. Mussel-Directed Synthesis of Nitrogen-Doped Anatase TiO2[J]. Angewandte Chemie International Edition, 2016, 55(9): 3031-3035). Wenhao Chi et al. used living clams to synthesize a two-phase uniformly distributed nano-SnO2 / graphene oxide composite material at room temperature. The structure has high loading and good uniformity. In addition, the obtained SnO2 / graphene oxide composite material exhibits excellent lithium storage performance as a negative electrode material for lithium-ion batteries. (W Chi, et al. Mussel directed synthesis of SnO2 / graphene oxide composite for energy storage[J]. Materials Chemistry Frontiers, 2021, 5(23): 8238-8247.). Previous studies have demonstrated the feasibility of guiding the room-temperature synthesis of inorganic materials based on natural biological platforms. However, these findings on the room-temperature synthesis of inorganic materials in vivo have not been able to further guide the synthesis of inorganic materials under environmentally friendly conditions in vitro. Therefore, it is necessary to further study the mechanisms by which organisms guide the room-temperature synthesis of inorganic materials and the biological functional elements that play a key role in the formation of inorganic materials. Furthermore, it is necessary to develop biomimetic room-temperature preparation technologies for inorganic materials in the laboratory, thereby providing new ideas and approaches for the room-temperature synthesis of inorganic functional materials.

[0004] Nano-iron oxide, a common functional metal oxide, exhibits outstanding optical, electrical, and magnetic properties and is widely used in energy, environmental, and biomedical fields. Hematite (α-Fe2O3) is a key member of the iron oxide family, and traditional iron oxide preparation often requires elevated temperatures. For example, traditional heat treatment often requires temperatures above 250°C, while hydrothermal synthesis requires temperatures above 160°C. Furthermore, as a functional inorganic oxide material, the mesoscopic structure of iron oxide enhances its performance. However, the synthesis of iron oxide meso-crystals often requires template etching and high-temperature treatment. Therefore, the green preparation of iron oxide meso-crystals remains a significant challenge. Organisms are capable of mineralizing and synthesizing inorganic materials at room temperature and pressure. By studying this biological process, innovative green synthesis methods for iron oxide meso-crystals are expected. Furthermore, developing room-temperature biomimetic synthesis techniques that utilize key biological functional elements within organisms to guide the biomimetic process of inorganic materials is of great significance. Summary of the Invention

[0005] The technical problem to be solved by the present invention is to provide a method for synthesizing iron oxide mesoscopic crystals by low-temperature mineralization of ferrihydrite, which utilizes ferrihydrite to mineralize at near room temperature to synthesize iron oxide inorganic materials, has low preparation cost, simple operation, energy saving and environmental protection.

[0006] The technical solution adopted by the present invention to solve the technical problem is to construct a method for synthesizing iron oxide mesoscopic crystals by low-temperature mineralization of ferrihydrite, comprising the following steps:

[0007] S1. Adding ferric nitrate nonahydrate to deionized water, reacting for a period of time in a constant temperature water bath with stirring, and then cooling to room temperature; collecting the precipitate by centrifugation, repeatedly washing with deionized water, and finally freeze-drying to obtain ferrihydrite powder; dispersing the ferrihydrite powder into an aqueous solution to obtain a ferrihydrite solution;

[0008] S2. Add ferric chloride and urea to deionized water and continue stirring to obtain a mineralized solution; add ferrihydrite solution dropwise under continuous stirring and continue stirring to obtain a mixed mineralized solution containing ferrihydrite; place the reactor containing the mixed mineralized solution in a constant temperature oven to fully react and then naturally cool to room temperature; collect the precipitate by centrifugation, repeatedly wash it with deionized water, and finally freeze-dry it to obtain an iron oxide mesoscopic crystal product.

[0009] According to the above scheme, in step S1, the concentration of ferric nitrate nonahydrate in the deionized solution is 8-10 g / L. The concentration of ferrihydrite in the ferrihydrite solution is 5-10 mg / mL;

[0010] According to the above scheme, in step S1, the temperature of the constant temperature water bath is 65-75° C., and the stirring time is 10-12 minutes.

[0011] According to the above scheme, in step S1, the centrifugal speed is 15000-17000 rpm, the centrifugal time is 10-20 min, the number of deionized water washings is three times, and the freeze-drying time is 24 h.

[0012] According to the above scheme, the concentration of ferric chloride in the mineralization solution is 0.8-1.2 M / L, the concentration of urea is 0.8-1.2 M / L, and the concentration of ferrihydrite in the mixed mineralization solution is 200-600 μg / mL.

[0013] According to the above scheme, in step S2, the stirring time is 10 to 12 minutes.

[0014] According to the above scheme, in step S2, the oven temperature is 60-100° C., and the reaction time is 24-96 hours.

[0015] According to the above scheme, in step S2, the centrifugal speed is 8000-9000 rpm, the centrifugal time is 10-20 min, the deionized water washing times are three times, and the freeze-drying time is 24 h.

[0016] The method of synthesizing iron oxide mesoscopic crystals by low-temperature mineralization of ferrihydrite according to the present invention has the following beneficial effects:

[0017] 1. This invention is the first to synthesize an inorganic iron oxide material using the biological functional element ferrihydrite at near room temperature, providing a new preparation method for low-energy and green preparation of iron oxide;

[0018] 2. The iron oxide synthesized in the present invention has typical mesoscopic crystal structure characteristics and uniform micromorphology, and is expected to be applied in the field of energy materials. The iron oxide mesoscopic crystals obtained under low-temperature mineralization have good lithium battery performance as anode materials for lithium batteries, indicating that this iron oxide has potential application value in energy materials.

[0019] 3. The preparation method of the present invention is simple and easy to operate, and provides an innovative method for the bionic room temperature preparation technology of inorganic materials. The preparation conditions are simple, and the particle size of the mineralized product is uniform. BRIEF DESCRIPTION OF THE DRAWINGS

[0020] The present invention will be further described below with reference to the accompanying drawings and embodiments, in which:

[0021] Figure 1 is a transmission electron image of ferrihydrite in Example 1 of the present invention;

[0022] Figure 2 is a scanning electron image of the iron oxide prepared in Example 1 of the present invention;

[0023] Figure 3Transmission electron image, HAADF-STEM image and electron diffraction image of the iron oxide prepared in Example 1 of the present invention;

[0024] Figure 4 The lithium battery cycle performance of the iron oxide prepared in Example 1 of the present invention;

[0025] Figure 5 is a scanning electron image of the iron oxide prepared in Example 2 of the present invention;

[0026] Figure 6 is a scanning electron image of the iron oxide prepared in Example 3 of the present invention;

[0027] Figure 7 is a scanning electron image of the iron oxyhydroxide prepared in Comparative Example 1 of the present invention;

[0028] Figure 8 is a scanning electron image of the iron oxyhydroxide prepared in Comparative Example 2 of the present invention;

[0029] Figure 9 is the XRD of the products synthesized in Examples 1, 2, 3 and Comparative Examples 1 and 2,

[0030] Among them, (a) Example 1, (b) Example 2, (c) Example 3, (d) Comparative Example 1, and (e) Comparative Example 2. DETAILED DESCRIPTION

[0031] In order to have a clearer understanding of the technical features, purposes and effects of the present invention, specific embodiments of the present invention are now described in detail with reference to the accompanying drawings.

[0032] The present invention provides a method for synthesizing iron oxide mesoscopic crystals by low-temperature mineralization of ferrihydrite, comprising the following steps: (1) adding ferric nitrate nonahydrate to deionized water, and then cooling to room temperature after reacting for a period of time in a constant temperature water bath; collecting the precipitate by centrifugation, repeatedly washing with deionized water, and finally freeze-drying to obtain ferrihydrite powder; dispersing the ferrihydrite powder into an aqueous solution to obtain a ferrihydrite solution. The concentration of ferric nitrate nonahydrate in the deionized solution is 8 to 10 g / L, the concentration of ferrihydrite in the ferrihydrite solution is 5 to 10 mg / mL, the constant temperature water bath temperature is 65 to 75°C, the stirring time is 10 to 12 minutes, the centrifugal speed is 15,000 to 17,000 rpm, the centrifugal time is 10 to 20 minutes, the number of deionized water washings is three times, and the freeze-drying time is 24 hours. (2) adding ferric chloride and urea to deionized water, and continuously stirring to obtain a mineralized solution. The ferrihydrite solution is added dropwise under continuous stirring, and stirring is continued to obtain a mixed mineralized solution containing ferrihydrite. The reactor containing the mixed mineralization solution is placed in a constant temperature oven for full reaction and then naturally cooled to room temperature. The precipitate is collected by centrifugation, repeatedly washed with deionized water, and finally freeze-dried to obtain an iron oxide mesocrystalline product. The concentration of ferric chloride in the mineralization solution is 0.8-1.2 M / L, the concentration of urea is 0.8-1.2 M / L, the concentration of ferrihydrite in the mixed mineralization solution is 200-600 μg / mL, the stirring time is 10-12 minutes, the oven temperature is 60-100°C, the reaction time is 24-96 hours, the centrifugal speed is 8000-9000 rpm, the centrifugal time is 10-20 minutes, the number of deionized water washes is three times, and the freeze-drying time is 24 hours.

[0033] Example 1

[0034] A method for synthesizing iron oxide mesoscopic crystals by low-temperature mineralization of ferrihydrite comprises the following steps:

[0035] (1) Add 2 g of ferric nitrate nonahydrate to 200 mL of deionized solution, then stir in a constant temperature water bath at 75°C for 10 min and cool to room temperature; centrifuge at 16,000 rpm for 20 min, wash three times with deionized water, and freeze-dry for 24 h to obtain ferrihydrite powder; disperse 10 mg of the ferrihydrite powder in 2 mL of deionized water to obtain a ferrihydrite solution with a concentration of 5 mg / mL;

[0036] (2) Add 0.8125 g of ferric chloride and 0.3 g of urea to 5 mL of deionized water, and continue stirring for 10 minutes to obtain a mineralization solution; add ferrihydrite solution dropwise under continuous stirring, and continue stirring for 20 minutes to obtain a mixed mineralization solution containing 300 μg / mL ferrihydrite; place the reactor containing the mixed mineralization solution in an oven at a temperature of 60°C, fully react for 96 hours, and then naturally cool to room temperature; centrifuge at a speed of 9000 rpm for 10 minutes, then repeatedly wash with deionized water three times, and freeze-dry for 24 hours to obtain an iron oxide mesoscopic crystal product.

[0037] like Figure 1 As shown in the figure, the structure of ferrihydrite was analyzed by transmission electron microscopy. The results showed that the synthesized ferrihydrite had a uniform particle size of about 25 nm. The mineralization product was detected by XRD and scanning electron imaging. The XRD results are shown in the figure. Figure 9 As shown in the curve a, the results show that the product synthesized under the guidance of ferrihydrite at 70℃ is a single iron oxide phase. Figure 2 As shown in the scanning electron image results, the results show that the synthesized iron oxide is a nanoparticle with a uniform particle size of about 150nm. Figure 3 As shown in the figure, the microstructure of iron oxide is observed by transmission electron microscopy. Iron oxide is assembled from nanoparticles. The electron diffraction of a single particle is a single crystal diffraction spot, and the diffraction point has a little tail, which is a typical mesoscopic crystal feature. Figure 4 As shown in the figure, the cycle performance of the iron oxide mesoscopic crystal of Example 1 as the negative electrode of lithium battery is -1 After 100 cycles at a current density of 1.5, the capacity still remained at 804.5 mA hg -1 , has good lithium battery performance, indicating that the iron oxide has potential application value in energy materials.

[0038] Example 2

[0039] A method for synthesizing iron oxide mesoscopic crystals by low-temperature mineralization of ferrihydrite comprises the following steps:

[0040] (1) 1.8 g of ferric nitrate nonahydrate was added to 200 mL of deionized water, followed by stirring in a 70°C constant temperature water bath for 10 min and cooling to room temperature. The mixture was centrifuged at 16,000 rpm for 20 min, washed three times with deionized water, and freeze-dried for 24 h to obtain ferrihydrite powder. 10 mg of ferrihydrite powder was dispersed in 1 mL of deionized water to obtain a ferrihydrite solution with a concentration of 10 mg / mL.

[0041] (2) Add 0.79 g of ferric chloride and 0.285 g of urea to 5 mL of deionized water and continue stirring for 10 minutes to obtain a mineralization solution. Add the ferrihydrite solution dropwise while continuing to stir, and continue stirring for 20 minutes to obtain a mixed mineralization solution containing 200 μg / mL ferrihydrite. Place the reactor containing the mixed mineralization solution in an oven at 80°C, allow to react for 48 hours, and then cool naturally to room temperature. Centrifuge at 9000 rpm for 10 minutes, then wash repeatedly with deionized water three times, and freeze-dry for 24 hours to obtain an iron oxide mesoscopic crystal product.

[0042] The mineralization products were detected by XRD and scanning electron imaging. The XRD results are as follows: Figure 9 As shown in curve b, the results show that the product synthesized under the guidance of ferrihydrite at 80℃ is a single iron oxide phase. Figure 5 As shown in the figure, the scanning electron image results show that the synthesized iron oxide is a nanoparticle with a uniform particle size of about 300 nm.

[0043] Example 3

[0044] A method for synthesizing iron oxide mesoscopic crystals by low-temperature mineralization of ferrihydrite comprises the following steps:

[0045] (1) 1.9 g of ferric nitrate nonahydrate was added to 200 mL of deionized water, followed by stirring in a 65°C water bath for 12 min and cooling to room temperature. The mixture was centrifuged at 16,000 rpm for 20 min, washed three times with deionized water, and freeze-dried for 24 h to obtain ferrihydrite powder. 10 mg of the ferrihydrite powder was dispersed in 2 mL of deionized water to obtain a ferrihydrite solution with a concentration of 5 mg / mL.

[0046] (2) Add 0.805 g of ferric chloride and 0.306 g of urea to 5 mL of deionized water and continue stirring for 10 minutes to obtain a mineralization solution. Add the ferrihydrite solution dropwise while continuing to stir, and continue stirring for 20 minutes to obtain a mixed mineralization solution containing 600 μg / mL ferrihydrite. Place the reactor containing the mixed mineralization solution in an oven at a temperature of 100°C, allow to react for 24 hours, and then naturally cool to room temperature. Centrifuge at a speed of 9000 rpm for 10 minutes, then wash repeatedly with deionized water three times, and freeze-dry for 24 hours to obtain an iron oxide mesoscopic crystal product.

[0047] The mineralization products were detected by XRD and scanning electron imaging. The XRD results are as follows: Figure 9 As shown in the curve c, the results show that the product synthesized under the guidance of ferrihydrite at 100 ° C is a single iron oxide phase. Figure 6 As shown, the scanning electron image results show that the synthesized iron oxide nanoparticles have a particle size of about 200 to 500 nm.

[0048] Comparative Example 1

[0049] The hydrothermal synthesis of iron oxyhydroxide guided by pure water includes the following steps:

[0050] Weigh 0.8125g of ferric chloride and 0.3g of urea into a beaker, add 5mL of deionized water, and stir continuously for 10 minutes to obtain a mineralization solution. Place the reactor containing the above solution in an oven at 70°C for 96 hours, then cool naturally to room temperature. Centrifuge at 9000rpm for 10 minutes, wash three times with deionized water, and freeze-dry for 24 hours to obtain the iron oxyhydroxide powder product.

[0051] The mineralization products were detected by XRD and scanning electron imaging. The XRD results are as follows: Figure 9 As shown in the curve d in the middle, the results show that the product synthesized at 70℃ with pure water is a single iron oxyhydroxide phase. The results of the comparative experiment with pure water show that iron oxide cannot be synthesized at a lower temperature of 70℃. The scanning electron image results are shown in Figure 7 As shown, the results show that the synthesized iron oxyhydroxide is a nanorod with a diameter of about 100 nm.

[0052] Comparative Example 2

[0053] The hydrothermal synthesis of iron oxyhydroxide guided by pure water includes the following steps:

[0054] Weigh 0.805g of ferric chloride and 0.31g of urea into a beaker, add 5mL of deionized water, and stir continuously for 10 minutes to obtain a mineralization solution. Place the reactor containing the above solution in an oven at 100°C for 48 hours, then cool naturally to room temperature. Centrifuge at 9000rpm for 10 minutes, wash three times with deionized water, and freeze-dry for 24 hours to obtain the iron oxyhydroxide powder product.

[0055] The mineralization products were detected by XRD and scanning electron imaging. The XRD results are as follows: Figure 9 As shown in the curve e, the results show that the product synthesized with pure water at 100 ° C is a single iron oxyhydroxide phase. The results of the comparative experiment with pure water show that iron oxide cannot be synthesized at a lower temperature of 100 ° C. The scanning electron image results are shown in Figure 8 As shown in the results, the synthesized iron oxyhydroxide is a nanorod with a diameter of about 100nm. Based on the above experimental results, iron oxide mesoscopic crystals were synthesized by mineralization of ferrihydrite at near room temperature.

[0056] In summary, the examples of the present invention demonstrate that the use of a ferrihydrite modifier enables the synthesis of iron oxide mesoscopic crystals at near room temperature, with simple preparation conditions and uniform particle size of the mineralized product. In contrast, in the comparative examples without the use of a ferrihydrite modifier, iron oxide could not be synthesized at near room temperature. The present invention provides an innovative preparation method for the low-temperature, low-energy synthesis of iron oxide materials.

[0057] The embodiments of the present invention are described above in conjunction with the accompanying drawings, but the present invention is not limited to the above-mentioned specific implementation methods. The above-mentioned specific implementation methods are merely illustrative and not restrictive. Under the guidance of the present invention, ordinary technicians in this field can also make many forms without departing from the scope of protection of the present invention and the claims, all of which are protected by the present invention.

Claims

1. A method for synthesizing iron oxide mesoscopic crystals by low-temperature mineralization of ferrihydrite, characterized in that: The following steps are involved: S1. Add ferric nitrate nonahydrate to deionized water, and then react for a period of time in a constant temperature water bath at 65-75° C. and then cool to room temperature; collect the precipitate by centrifugation, wash it repeatedly with deionized water, and finally freeze-dry it to obtain ferrihydrite powder; disperse the ferrihydrite powder in an aqueous solution to obtain a ferrihydrite solution; S2. Add ferric chloride and urea to deionized water, and continue stirring to obtain a mineralized solution; add ferrihydrite solution dropwise under continuous stirring, and continue stirring to obtain a mixed mineralized solution containing ferrihydrite; place the reactor containing the mixed mineralized solution in a constant temperature oven at 60-100°C for sufficient reaction and then naturally cool to room temperature; collect the precipitate by centrifugation, wash it repeatedly with deionized water, and finally freeze-dry it to obtain an iron oxide mesoscopic crystal product.

2. The method for synthesizing iron oxide mesoscopic crystals by low-temperature mineralization of ferrihydrite according to claim 1, characterized in that: In the step S1, the concentration of ferric nitrate nonahydrate in the deionized solution is 8-10 g / L, and the concentration of ferrihydrite in the ferrihydrite solution is 5-10 mg / mL.

3. The method for synthesizing iron oxide mesoscopic crystals by low-temperature mineralization of ferrihydrite according to claim 2, characterized in that: In step S1, the stirring time is 10 to 12 minutes.

4. The method for synthesizing iron oxide mesoscopic crystals by low-temperature mineralization of ferrihydrite according to claim 3, characterized in that: In the step S1, the centrifugal speed is 15000-17000 rpm, the centrifugal time is 10-20 min, the number of deionized water washing is three times, and the freeze-drying time is 24 h.

5. The method for synthesizing iron oxide mesoscopic crystals by low-temperature mineralization of ferrihydrite according to claim 1, characterized in that: The concentration of ferric chloride in the mineralization solution is 0.8-1.2 M / L, the concentration of urea is 0.8-1.2 M / L, and the concentration of ferrihydrite in the mixed mineralization solution is 200-600 μg / mL.

6. The method for synthesizing iron oxide mesoscopic crystals by low-temperature mineralization of ferrihydrite according to claim 5, characterized in that: In step S2, the stirring time is 10 to 12 minutes.

7. The method for synthesizing iron oxide mesoscopic crystals by low-temperature mineralization of ferrihydrite according to claim 6, characterized in that: In step S2, the reaction time is 24 to 96 hours.

8. The method for synthesizing iron oxide mesoscopic crystals by low-temperature mineralization of ferrihydrite according to claim 7, characterized in that: In the step S2, the centrifugal speed is 8000-9000 rpm, the centrifugal time is 10-20 min, the number of deionized water washing is three times, and the freeze-drying time is 24 h.

Citation Information

Patent Citations

  • Method of preparing monodisperse iron oxide quasi-cubic mesoscopic crystal with adjustable grain size

    CN103482708A